A pilot study of changes in urinary podocalyxin levels during normal pregnancy and labor - De Franco Ylbe Palacios; Segovia Natalia; Marx Ylbe Franco; Hoxhaj Rudiona; Palacios Carlos Franco (Sciendo, 2022)
Introduction: Increased urinary podocalyxin, a surrogate marker of podocyte detachment, has been shown in preeclampsia and eclampsia, but there is a paucity of data of the effect of normal pregnancy on its urinary excretion. We aimed to describe these changes in this pilot study.